2001
DOI: 10.1073/pnas.211440698
|View full text |Cite
|
Sign up to set email alerts
|

Translation of chloroplast psbA mRNA is regulated by signals initiated by both photosystems II and I

Abstract: Light controls the translation of several mRNAs in fully developed chloroplasts via at least two regulatory pathways. In the first, the light signal is transduced as a thiol-mediated signal that modulates translation in parallel to light intensity. The second light-controlled pathway, termed priming, is a prerequisite to the thiol-mediated regulatory pathway. Light regulation is rapid and requires intrachloroplast photoreceptor(s). To delineate the signaling pathways controlling each of these regulatory events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 55 publications
5
74
0
Order By: Relevance
“…Figure 4 also shows that DCMU depressed the level of psbA transcripts by approximately 50% at all light intensities examined. These results are consistent with those in previous reports (Alfonso et al, 1999;Sippola and Aro, 2000;Zhang et al, 2000;Trebitsh and Danon, 2001) and they suggest that inhibition of electron transport by DCMU blocked, in part, the synthesis of the psbA transcripts. The further addition of DCCD eliminated the synthesis of psbA transcripts, suggesting that the 50% level of psbA transcripts, We monitored changes in levels of psbA mRNAs due to the presence of inhibitors and other reagents (Fig.…”
Section: Inhibition Of Electron Transport In Psii and Of Atp Synthesisupporting
confidence: 94%
See 1 more Smart Citation
“…Figure 4 also shows that DCMU depressed the level of psbA transcripts by approximately 50% at all light intensities examined. These results are consistent with those in previous reports (Alfonso et al, 1999;Sippola and Aro, 2000;Zhang et al, 2000;Trebitsh and Danon, 2001) and they suggest that inhibition of electron transport by DCMU blocked, in part, the synthesis of the psbA transcripts. The further addition of DCCD eliminated the synthesis of psbA transcripts, suggesting that the 50% level of psbA transcripts, We monitored changes in levels of psbA mRNAs due to the presence of inhibitors and other reagents (Fig.…”
Section: Inhibition Of Electron Transport In Psii and Of Atp Synthesisupporting
confidence: 94%
“…In Chlamydomonas, Trebitsh and Danon (2001) showed that the redox signal associated with electron transport in PSI, as well as reduction of the plastoquinone pool, activated the initiation of translation of the D1 protein. Studies in intact chloroplasts from spinach showed that the level of stromal ATP was correlated with the light-dependent synthesis of the D1 protein in intact chloroplasts (Kuroda et al, 1992).…”
mentioning
confidence: 99%
“…Recent results demonstrate that this light activation is mediated by two signals: a 'priming' signal generated by the PQ pool and a dithiol signal from thioredoxin. The priming signal regulates an oxidation activity that has yet to be identified, which oxidizes the protein complex, making it susceptible to reduction by thioredoxin [26]. Inactivation of complex-binding activity in the dark is mediated by phosphorylation through an ADPdependent protein kinase [27] and it is hypothesized that, by this mechanism, high ADP levels in chloroplasts in the dark inhibit psbA translation and that a high content of reducing equivalents in the light promote its translation.…”
Section: Inner-chloroplastic Transduction Of Photosynthetic Redox Sigmentioning
confidence: 99%
“…Manipulation of photosynthetic electron transport by light sources that predominately excite either PSI or [26]. In its reduced active form, PDI then transmits its SH-group signal to PABP, resulting in an increased binding activity that finally leads to an increased translation of the message.…”
Section: Redox Signalling Pathways In Cyanobacteria -A Model For Chlomentioning
confidence: 99%
“…If not regulated properly, the conversion of light energy into photosynthetic linear electron flow can turn in a short period of time into excessive production of deleterious reactive oxygen species (ROS). Perhaps because of the short time response needed, plants use photosynthetic redox signals as a direct and dynamic means to regulate multiple chloroplast phenomena, controlling the production of reducing equivalents and alleviating their inflicted damage (Karpinski et al, 1999;Trebitsh and Danon, 2001;Pfannschmidt, 2003;Rochaix, 2007;Schürmann and Buchanan, 2008). Yet, the mechanisms by which the redox signals are sensed are only beginning to unravel.…”
Section: Introductionmentioning
confidence: 99%